2013
DOI: 10.7748/mhp2013.11.17.3.34.e827
|View full text |Cite
|
Sign up to set email alerts
|

Staff attitudes towards inpatients with borderline personality disorder

Abstract: This paper discusses negative attitudes of mental health nurses towards

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Numerous studies have opined that clinicians and medical staff project a negative attitude for patients with BPD, more so for patients with self-damage or suicidal attitude ( 43 45 ). The main reasons for negative attitude include the stigma toward BPD, patients are considered as manipulative, lack of optimism for recovery, work pressure, poor communication skills, and time restraints ( 43 , 46 ).…”
Section: Approach Toward Bpd Patientsmentioning
confidence: 99%
“…Numerous studies have opined that clinicians and medical staff project a negative attitude for patients with BPD, more so for patients with self-damage or suicidal attitude ( 43 45 ). The main reasons for negative attitude include the stigma toward BPD, patients are considered as manipulative, lack of optimism for recovery, work pressure, poor communication skills, and time restraints ( 43 , 46 ).…”
Section: Approach Toward Bpd Patientsmentioning
confidence: 99%
“…Amongst qualified staff, reluctance to ask about sexual abuse and lack of training to work with this issue has been identified (Hepworth and McGowan, 2013;Tong and Gillespie, 2011). Several authors have identified problems surrounding nurse attitudes to service users with a diagnosis of personality disorder as well as a lack of training and supervision to work therapeutically with this group (Weight and Kendal, 2013;O'Connell and Dowling, 2013;Westwood and Baker, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A need to develop skills in working with BPD was also a theme evident within the literature reviewed by Westwood & Baker (2010). Despite emerging evidence toward efficacy of specific treatments (NICE, 2009), negative attitudes and skill deficits are likely to impact in a detrimental way on clinical practice, leading some advocates to call for additional training for mental health staff in both the diagnosis of BPD and also in communicating with service users with the diagnosis (Weight & Kendal 2013). Developing optimistic, trusting relationships which foster choice and autonomy are important factors (NICE 2009), and are likely to underpin the success of specific treatments offered by mental health services.…”
Section: Introductionmentioning
confidence: 99%